Antimetabolic Effects of Polyphenols in Breast Cancer Cells: Focus on Glucose Uptake and Metabolism - Keating, Elisa; Martel, Fátima (Frontiers in Nutrition, 2018)
In the last years, metabolic reprogramming became a new key hallmark of tumor cells. One of its components is a deviant energetic metabolism, known as Warburg effect - an aerobic lactatogenesis - characterized by elevated rates of glucose uptake and consumption with high lactate production even in the presence of oxygen. The fact that many cancer cells display a greater sensitivity to glucose deprivation-induced cytotoxicity than normal cells explain why inhibitors of glucose transporters (GLUT1 inhibitors) and oxidative metabolism (glycolysis inhibitors) are potential therapeutic targets in cancer treatment. Polyphenols, commonly contained in fruits and vegetables, are dietary components with an established protective role against cancer. The molecular mechanisms of anti-cancer effects of polyphenols are related to apoptosis, cell cycle regulation, plasma membrane receptors, signaling pathways and epigenetic mechanisms. Additionally, in vitro studies have shown that several polyphenols act as specific inhibitors of glucose transport and metabolism by breast cancer cell lines and an association between their anticarcinogenic effect and inhibition of glucose cellular uptake and metabolism has been described. Herein, we will review the antimetabolic effect of polyphenols, which should be regarded as a mechanism of action contributing to their chemopreventive/chemotherapeutic potential, in relation to breast cancer.